2021
DOI: 10.3390/ijms22147619
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Associated with Organ-Specific Involvement in Juvenile Systemic Lupus Erythematosus

Abstract: Juvenile systemic lupus erythematosus (JSLE) is characterised by onset before 18 years of age and more severe disease phenotype, increased morbidity and mortality compared to adult-onset SLE. Management strategies in JSLE rely heavily on evidence derived from adult-onset SLE studies; therefore, identifying biomarkers associated with the disease pathogenesis and reflecting particularities of JSLE clinical phenotype holds promise for better patient management and improved outcomes. This narrative review summaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 238 publications
(427 reference statements)
0
12
0
Order By: Relevance
“…Therefore, the findings have limited applicability in JSLE. In addition, the complexity of the pathogenesis for JSLE suggests the need for research targeting young patients rather than adult patients [ 38 ]. In the present study, we aimed to investigate the lymphocyte subsets (CD4 + T cells, CD8 + T cells, γδ T cells, Tregs, CD19 + B cells, NK cells, and NKT cells) in JSLE patients and determine their associations with clinical phenotypes and disease activity, as well as long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the findings have limited applicability in JSLE. In addition, the complexity of the pathogenesis for JSLE suggests the need for research targeting young patients rather than adult patients [ 38 ]. In the present study, we aimed to investigate the lymphocyte subsets (CD4 + T cells, CD8 + T cells, γδ T cells, Tregs, CD19 + B cells, NK cells, and NKT cells) in JSLE patients and determine their associations with clinical phenotypes and disease activity, as well as long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ORM has been studied as a potential blood biomarker for many diseases (28)(29)(30)(31). ORM has also been studied as a single or combined urinary biomarker of inflammatory diseases and cancer, including lupus nephritis, adult-onset Still's disease, psoriasis, rheumatoid arthritis, sepsis, Crohn's disease, bladder cancer, and hepatocellular carcinoma (32)(33)(34)(35)(36)(37)(38). In one cohort study, urinary ORM showed a significant association with incident hypertension at the 7-year follow-up (39).…”
Section: Discussionmentioning
confidence: 99%
“…Third, due to the retrospective study design, there was an absence of the British Isles Lupus Assessment group index (BILAG) or the Systemic Lupus International Collaborating Clinics damage index (SDI), genomic variants 26 and serological data, such as cytokines. 27 Appropriate advanced biomarkers 28…”
Section: Discussionmentioning
confidence: 99%